The Environmental Impact of Bertrand and Cournot Duopolies. A Cautionary Note - Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
We compare a Bertrand with a Cournot duopoly in a setting where production is polluting and exploits natural resources, and firms bear convex production costs. We adopt Dastidar's (1995) approach, yielding a continuum of Bertrand-Nash equilibria ranging above marginal cost pricing also, to show that softening price competition may lead to a lower output production in a Bertrand rather than a Cournot industry. The market structure bringing about the lowest output determines the highest social welfare, given the fact that the negative environmental effects of production more than offset the gain in consumer surplus.
Keywords: L13; L51; Q55; Q58; 330